Influencia Del Nivel De Instrucción En La Capacidad Emprendedora - Apolo, Mario Beltrán; Molina, Andrés Pacheco; Orellana, Bill Serrano; Brito-Gaona, Luis (European Scientific Journal, ESJ, 2016)
This research analyzed the influence of the level of education in entrepreneurship. The study included 982 participants in Machala-Ecuador. A survey with 20 questions to help determine the entrepreneurial ability to then provide a statistical analysis through a linear regression model, analysis where the dependent variable is quantitative and the independent variable is dichotomous. The results indicate a significant relationship between the level of education and entrepreneurship, as well as in each of the five dimensions involved. It is concluded that the ability for individuals to undertake entrepreneurship is proportional to the level of education they posses. These findings may be useful for both the general population as well as public or private institutions which employ mechanisms to promote both management and development of enterprises.